The effect of polyethylene glycol on the charcoal adsorption of chlorpromazine studied by ion selective electrode potentiometry - AttaPolitou, J; Macheras, PE; Koupparis, MA (JOURNAL OF TOXICOLOGY-CLINICAL TOXICOLOGY, 1996)
Background: This investigation war undertaken to study: a) the adsorption characteristics of chlorpromazine to activated charcoal and its formulations Carbomix(R) powder and Ultracarbon(R) tablets at gastric pH; b) the effect on chlorpromazine adsorption of polyethylene glycol and its combination with electrolyte lavage solution; c) the effect of the order of addition of polyethylene glycol-electrolyte lavage solution. Method: Ion selective electrode potentiometry, bared on the selective, direct and continuous response of a chlorpromazine-ion selective electrode to the concentration of the free drug, was used. Successive additions of microvolumes of a chlorpromazine solution were made into a charcoal slurry in acidic medium of pH 1.2 with measurement of the chlorpromazine-ion selective electrode potential at equilibrium Results: The maximum adsorption capacity values of activated charcoal, Carbomix and Ultracarbon, were 297, 563, and 382 mg/g respectively, while the affinity constant values were 40.2, 70.4, and 40.5 L/g, respectively. The adsorption of chlorpromazine to each of the Ultracarbon and Carbomix components was compared to the total adsorption of the formulations. The addition of polyethylene glycol-electrolyte lavage solution causes a slight desorption of chlorpromazine from activated charcoal at gastric pH, more pronounced when polyethylene glycol-electrolyte lavage solution follows the addition of activated charcoal, suggesting the possibility of a nonspecific binding of chlorpromazine to polyethylene glycol. The amount of chlorpromazine adsorbed to Carbomix and Ultracarbon was not significantly affected at gastric pH by the presence of polyethylene glycol or polyethylene glycol-electrolyte lavage solution added either concurrently or sequentially to these formulations.